Light-induced inhibition of laccase in Pycnoporus sanguineus - Hernández, Christian A; Perroni, Yareni; Pérez, José Antonio García; Rivera, Beatriz Gutiérrez; Alarcón, Enrique (Folia microbiologica, 2016)
The aim was to determine which specific regions of the visible light spectrum were responsible for the induction or inhibition of laccase in Pycnoporus sanguineus. Cultures were exposed to various bandwidth lights: blue (460 nm), green (525 nm), white (a combination of 460 and 560 nm), red (660 nm), and darkness. The results indicate that short wavelengths strongly inhibit the production of laccase: green (3.76 ± 1.12 U/L), blue (1.94 ± 0.36 U/L), and white (1.05 ± 0.21 U/L) in proportions of 85.8, 92.6, and 96.0%, respectively; whereas long wavelengths inhibit laccase production only partially i.e., red light (14.05 ± 4.79 U/L) in a proportion of 46.8%. Maximum activity was induced in absence of visible light (30 °C, darkness), i.e., 30.76 ± 4.0 U/L. It is concluded that the production of laccase in P. sanguineus responds to light stimuli [measured as wavelengths and lx] and that it does so inversely. This can be explained as an ecological mechanism of environmental recognition, given that P. sanguineus develops inside lignocellulose structures in conditions of darkness. The presence of short wavelength light (460-510 nm) would indicate that the organism finds itself in an external environment, unprovided of lignin, and that it is therefore unnecessary to secrete laccase. This possible new regulation in the laccase production in P. sanguineus has important biotechnological implications, for it would be possible to control the production of laccase using light stimuli.
Keywords: lakasa; Laccase; Light; Fungal Proteins; světlo; fungální proteiny; Pycnoporus